Thyroid nodule rupture after radiofrequency ablation: case report and literature review - Ferraro, Tatiana; Sajid, Sameeha; Hodak, Steven P.; Baldwin, Chelsey K. (Frontiers in Endocrinology, 2024)
Purpose: Radiofrequency ablation (RFA) is an effective and safe modality for the treatment of thyroid nodules. Nodule rupture is a major complication of RFA. There is little known on the natural history of nodule rupture due to a lack of clinical experience and no consensus on its management. A comprehensive review of nodule rupture presentation, diagnosis, and management is needed.We report a case of nodule rupture and conduct a literature review. Thirty-three patients experiencing nodule rupture after RFA were included and their clinical presentation, management and outcomes were collected and analyzed.Results: Nodule rupture presents with acute swelling (90.3%) and pain (77.4%) within 7 months of RFA procedure, most commonly due to disruption of the anterior thyroid capsule (87%) and can be diagnosed with ultrasonography. Most ruptures can be managed conservatively, exemplified by our reported case. There are no reported cases of long term sequalae.Nodule rupture is the second most common major complication of RFA. Based on the available evidence, we propose a treatment algorithm for nodule rupture and recommendations for future data collection to address gaps in our understanding of rupture etiology and effective management.